Demystifying Orchid Pollination: back to the basics of Natural History - Avalos, Gerardo (Universidad de Costa Rica, 2023)
Karremans, A. P. (2023). Demystifying Orchid Pollination. Kew Publishing, Royal Botanical Gardens, Kew, Richmond, Surrey, TW9 3AB UK, 440 pp.